Maximal tumor diameter in the preoperative tumor magnetic resonance imaging (MRI) T2 image is associated with prognosis of Grade II Glioma. Issue 10 (12th March 2021) - Liu, Haipeng; Shen, Liangfang; Huang, Xinqiong; Zhang, Guangying
Abstract : Abstract: Factors associated with the prognosis of low-grade glioma remain undefined. In this study, we examined whether the maximal tumor diameter in the preoperative tumor magnetic resonance imaging (MRI) T2 image is associated with the prognosis of grade II gliomas patients, aiming to provide insights into the clinical prediction of patient outcome. We retrospectively analyzed the clinical data of patients with Grade II glioma, who were hospitalized in Xiangya Hospital, Central South University, from 2011 to 2016. Kaplan–Meier and Cox proportional hazards analyses were performed to determine the association between maximal tumor diameter and prognosis. A total of 90 patients with grade II glioma were included in this study. Mean patient age was 37.7 ± 13.0 years, and 58.9% of them were male. Kaplan–Meier survival analysis of overall survival (overall survival [OS], P = .009) and event-free survival (EFS, P = .002) revealed statistically significant differences between the patients with lesion diameter <7 cm and those with lesion diameter ≥7 cm. The maximal tumor diameter in the preoperative tumor MRI T2 image was identified as a prognostic factor of OS ( P = .013), while constituting an independent risk factor for EFS ( P = .002) alongside elevated histological grade after recurrence ( P = .006). The maximal tumor diameter in the preoperative tumor MRI T2 image independently predicts OS and EFS in patients with grade II glioma.